The spectrum of leukodystrophies in children: Experience at a tertiary care centre from North India - Gulati, Sheffali (Ann Indian Acad Neurol, 2016)
OBJECTIVE: The objective of this study is to retrospectively collect and then describe the clinico-radiographical profile of confirmed cases of leukodystrophy who presented over a 5-year period to a tertiary care teaching hospital in North India. MATERIALS AND METHODS: The case records of 80 confirmed cases of leukodystrophy were reviewed and the cases have been described in terms of their clinical presentation and neuroimaging findings. RESULTS: The cases have been grouped into five categories: Hypomyelinating, demyelinating, disorders with vacuolization, cystic, and miscellaneous. The commonest leukodystrophies are megalencephalic leukoencephalopathy with subcortical cysts (MLC), Pelizaeus-Merzbacher disease (PMD), and metachromatic leukodystrophy (MLD). A notable proportion of hypomyelinating disorders were uncharacterized. CONCLUSIONS: Leukodystrophies at this point of time have no definite cure. They have a progressively downhill clinical course. Early diagnosis is imperative for appropriate genetic counseling. A simplified approach to diagnose common leukodystrophies has also been provided. It is important to develop a registry, which can provide valuable epidemiological data to prioritize research in this field, which has many unanswered questions.